2017
DOI: 10.1186/s12859-016-1418-6
|View full text |Cite
|
Sign up to set email alerts
|

Confident gene activity prediction based on single histone modification H2BK5ac in human cell lines

Abstract: BackgroundThe histones in the core of nucleosomes may be subject to covalent post-transcriptional modifications. These modifications are thought to correlate with and possibly affect various genomic functions, including transcription. Each modification may alone or in combination with other modifications influence or be influenced by transcription. We aimed to identify correlations between single modifications or combinations of modifications at specific nucleosome sized gene regions with transcription activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Studies elucidating the roles of histone H2B in asthma are limited. Despite the correlation of H2BK5ac and asthma has not been demonstrated, recent data suggested that EMT is regulated by H2BK5ac, 32,33 thus we speculated that H2BK5ac participated in the pathogenesis of asthma via regulating EMT. Besides, H2BK20ac and H2BK120ac have been proven a strong correlation with DNA methylation, 34 which hinted that they may regulate gene expression to affect disease development.…”
Section: Discussionmentioning
confidence: 78%
“…Studies elucidating the roles of histone H2B in asthma are limited. Despite the correlation of H2BK5ac and asthma has not been demonstrated, recent data suggested that EMT is regulated by H2BK5ac, 32,33 thus we speculated that H2BK5ac participated in the pathogenesis of asthma via regulating EMT. Besides, H2BK20ac and H2BK120ac have been proven a strong correlation with DNA methylation, 34 which hinted that they may regulate gene expression to affect disease development.…”
Section: Discussionmentioning
confidence: 78%
“…To test the ability of PROTACs to penetrate cells and inhibit class I HDACs, we measured lysine acetylation levels in histone tails. We examined two independent sites of acetylation, Lys56 on histone H3 (H3K56ac), a known HDAC1/2 substrate, 34 and Lys5 on histone H2B (H2BK5ac), a mark of active transcription, 35 by quantitative Western blotting ( Figure 2 B). Treatment of cells with CI-994 produced robust 20- and 15-fold increases in H3K56ac and H2BK5ac levels, respectively, compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data suggest that H2BK5ac is a reliable predictor of gene expression [ 51 ] and an important modifier in the orchestration of EMT programs. Mechanistically, MAP3K4-regulated chromatin modifiers CBP and HDAC6 each regulate thousands of genes during EMT by controlling promoter acetylation of H2BK5 [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%